INFORMATION SYSTEMS ADOPTION AND USE BEHAVIOR OF QRIS AS A DIGITAL PAYMENT INFRASTRUCTURE AMONG GENERATION Z - Sugiarto, Adrian Herma; Maria, Evi; Nataliani, Yessica (LPPM Universitas Jambi, 2026)
Financial technology transformation has positioned QRIS as a core component of the Indonesia’s digital payment infrastructure. This study aims to examine the determinants of QRIS usage among Generation Z in Indonesia by extending the UTAUT2 framework. The novelty of this study lies in the integration of Personal Innovativeness to capture internal psychological dimensions in the adoption of a mature national payment system among digital-native users. Quantitative data were collected from 261 Generation Z respondents through questionnaires and analyzed using the SEM-PLS method to evaluate both measurement and structural models. The findings show that Social Influence, Habit, and Personal Innovativeness significantly predict Behavioral Intention. In contrast, utilitarian constructs (Performance Expectancy, Effort Expectancy, Hedonic Motivation, Price Value) are not significant. Additionally, Facilitating Conditions exhibit a significantly negative effect, suggesting that reliance on technical infrastructure is not perceived as a motivating factor. These findings indicate that social and habitual factors play a more prominent role than utilitarian considerations in shaping QRIS usage intention. Functional aspects are increasingly perceived as baseline expectations, while adoption is more strongly influenced by established usage patterns and individual innovativeness. This study suggests that policymakers and service providers should shift their strategic focus from functional promotion toward socially embedded and community-based approaches to strengthen user engagement and sustained adoption.